Arthur Benjamin, Gary Chartrand and Ping Zhang; The Fascinating World of Graph Theory, Princeton University Press, Princeton NJ, 2015, xii+322 p., ISBN 978-0-691-16381-9/hbk; 978-1-4008-5200-0/ebook). - TRÎMBIŢAŞ, Radu (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The book is designed to introduce the field of Graph Theory to a broad audience and to also serve as an introductory textbook. Although the content is traditional for an undergraduate course, the way of presentation is not: the authors manage to motivate all topics with interesting applications, historical problems and discussion of concepts from an intuitive point of view.